Breakthrough pain among cancer patients at oncology units in Northern Ethiopia; a multi-center study - Tekie, Yohanes; Nigatu, Yonas Addisu; Mekonnen, Wudie; Berhe, Yophtahe Woldegerima (Frontiers in Oncology, 2024)
Background: Breakthrough cancer pain (BTCP) is a transient exacerbation of pain that affects the length of hospitalization and quality of life. The objective of this study was to determine the prevalence and factors associated with BTCP among cancer patients at oncology units in Northern Ethiopia, 2022.A multi-center cross-sectional study was conducted from April to June 2022.After obtaining ethical approval, data were collected prospectively from 424 adult cancer patients admitted to oncology units. Breakthrough cancer pain was assessed by the numeric rating scale. Descriptive and binary logistic regression analysis were performed to determine the factor associated with BTCP. Strength of association was described in adjusted odds ratio (AOR) with 95% confidence intervals; and variables with a P-value < 0.05 were considered to have statistically significant association with BTCP.The prevalence of BTCP among cancer patients was 41.5%. Factors that were found associated with BTCP were colorectal cancer (AOR: 7.7, 95% CI: 1.8, 32.3), lung cancer (AOR: 6.9, 95% CI: 1.9, 26.0), metastasis (AOR: 9.3, 95% CI: 3.0, 29.1), mild background pain (AOR: 7.5, 95% CI: 2.5, 22.6), moderate background pain (AOR: 7.0, 95% CI: 2.2, 23.1), severe background pain (AOR: 7.1, 95% CI: 2.2, 22.8), no analgesics took for background pain (AOR: 5.1, 95% CI: 2.8, 9.3) and uncontrolled background pain (AOR: 3.3, 95% CI: 1.8, 6.1).The prevalence of BTCP was high. Colorectal cancer, lung cancer, presence of metastasis, presence of background pain, not taking analgesics for background pain, and uncontrolled background pain were significantly associated with BTCP.